(untitled) (Journal of the College of Basic Education, 2022)
The rapid development and development of knowledge and development led to the inclusion of societies in great psychological, social and cultural challenges, which made them witness a radical change that almost ravages their dress, their cultural and values ​​heritage, and they were affected to varying degrees by the forces of change as this development was accompanied by great upheavals (Al-Khalidi 2012: 9).